ANALISIS HARGA POKOK PRODUKSI MENGGUNAKAN METODE FULL COSTING SEBAGAI DASAR PENENTUAN HARGA JUAL - Yunanda Prameswari (Commodities, Journal of Economic and Business, 2024)
A company needs to calculate the cost of production, because the cost of production is one of the factors that influence the determination of selling prices. In order to produce normative costs, an appropriate method is needed. One method that can be used in determining the cost of production is the full costing method. This research was conducted at Uyel cracker company UD. SUWARDI (SWD) Kediri. The purpose of this study is to produce how much the normative selling price of uyel crackers at UD. SWD Kediri. The type of research used is descriptive quantitative. The results of the study are the calculation of the cost of production carried out by the company UD. SWD Kediri for 2017 is Rp. 15,619 and 2018 amounting to Rp. 16,056. While the results of the analysis of the calculation of the cost of production with the full costing method for 2017 amounted to Rp. 17,295 and 2018 amounting to Rp. 17,769. The difference between the full costing method and the method carried out by the company for 2017 is Rp. 1,676 and 2018 amounting to Rp. 1,713. Based on the results of the study it can be concluded that the calculation of cost of production as a basis for determining the selling price using the full costing method is better because this method calculates all costs incurred in the production process.